A novel immunomodulatory function of neutrophils on rhinovirus-activated monocytes in vitro. Issue 11 (10th June 2016) - Tang, Francesca S M; Hansbro, Philip M; Burgess, Janette K; Ammit, Alaina J; Baines, Katherine J; Oliver, Brian G
Abstract : Background: Rhinovirus (RV) infections are the major precipitant of asthma exacerbations. While neutrophilic lung inflammation occurs during such infections, its role remains unclear. Neutrophilic inflammation is associated with increased asthma severity and steroid refractory disease. Neutrophils are vital for controlling infections but also have immunomodulatory functions. Previously, we found that neutrophils respond to viral mimetics but not replication competent RV. We aimed to investigate if neutrophils are activated and/or modulate immune responses of monocytes during RV16 infection. Methods: Primary human monocytes and autologous neutrophils were cocultured with or without RV16, in direct contact or separated by transwells. RV16-stimulated monocytes were also exposed to lysed neutrophils, neutrophil membrane components or soluble neutrophil intracellular components. Interleukin 6 (IL-6) and C-X-C motif (CXC)L8 mRNA and proteins were measured by quantitative PCR and ELISA at 24 hours. Results: RV16 induced IL-6 and CXCL8 in monocytes, but not neutrophils. RV16-induced IL-6 and CXCL8 from monocytes was reduced in the presence of live neutrophils. Transwell separation abolished the inhibitory effects. Lysed neutrophils inhibited RV16-induced IL-6 and CXCL8 from monocytes. Neutrophil intracellular components alone effectively inhibited RV16-induced monocyte-derived IL-6 and CXCL8. Neutrophil intracellular components reduced RV16-induced IL-6 and CXCL8 mRNA in monocytes. Conclusions: Cell contact between monocytes and neutrophils is required, and preformed neutrophil mediator(s) are likely to be involved in the suppression of cytokine mRNA and protein production. This study demonstrates a novel regulatory function of neutrophils on RV-activated monocytes in vitro, challenging the paradigm that neutrophils are predominantly proinflammatory.